Using “Closed Group” Facebook to teach writing for the tenth graders of SMAN 1 Jiwan - Lilis Suganda (Universitas PGRI Madiun, 2018)
This research aims at improving the writing learning process of the tenth graders of SMA Negeri 1 Jiwan through closed group Facebook. This research used descriptive qualitative research and data collected using methodological triangulation. Then, to collect the data, researcher needs a technique that is called technique of collecting data. There were observation, interview and documentation.Based on the result of this research, Closed Group Facebook is more interesting than write on paper, helps the students to active in teaching writing, makes easier to share problem in their writing, can increase the students’ interest to learn writing, makes the students easily understand their mistake in writing by giving friend’s feedback in the comment, makes the students enjoy in learning writing.Meanwhile, the disadvantages are first, Closed Group Facebook only can be accessed if there is quota internet or access wi-fi. The second, students’ activity can not be controlled by the teacher when they are opening Facebook or when they operate their gadget. It can be concluded that using closed group Facebook can improve students’ writing skill. The last, the researcher also gives the suggestion for the teacher, students, school, and future researcher that they should do better research.